Manajemen Kesehatan Ternak Babi yang Berdampak pada Penyebaran African Swine Fever di Kupang, Nusa Tenggara Timur - Bulu, Petrus Malo; Wera, Ewaldus; Kaka, Hendrina Lero (Jurnal Veteriner; Vol 23 No 4 (2022)DO - 10.19087/jveteriner.2022.23.4.558, 2022)
African Swine Fever (ASF) is a disease in pigs of all ages caused by a virus from the Asfar virus family, and the virus is classified as an economically important pathogen group.  This disease has caused the death of pigs in Nusa Tenggara Timur Province including Kupang Regency.  The spread of ASF disease can occur when the animal health management is poor.  Little was known about the health management of pigs in the district of Kupang. Therefore, this study was aimed to identify factors of health management which potentially affect the spread of ASF in the district of Kupang.  This research was conducted in two selected sub-districts in Kupang Regency, namely East Kupang District and Amabi Oefeto District.  The selection of these sub-districts was based on the results of discussions with the Head of the Livestock Service Office of Kupang Regency, where these two sub-districts became centers of pig production.  The results showed that the health management of pigs in the selected sub-districts of Kupang Regency was still very poor among vehicle and people traffic control, disease control, livestock waste, sanitation and disinfection, pest control, pig traffic, pig marketing, health status and ASF, disposal system pig carcasses, and contact between pigs.